A Historical Perspective on WRESAT, the First Satellite Launched from Australian Soil - Forbes, Allan (Journal of Telecommunications and the Digital Economy, 2018)
Just over fifty years ago, on 29 November 1967 at 2:19 pm (local time), a small scientific satellite named the Weapons Research Establishment SATellite (WRESAT) was launched from Woomera, South Australia. It had been designed and constructed by engineers, scientists and technicians from the Weapons Research Establishment, Salisbury, South Australia; it had a payload of scientific instruments put together by the Physics Department at Adelaide University; and it was sent into orbit at the sharp end of a modified Redstone rocket, a gift from the United States. All of this was achieved in less than 12 months; and it made Australia the third country in the world to launch a satellite into space from its own territory, after the USSR and the USA. This paper is the author’s personal account of his part in the project, where he was involved first with the satellite’s telemetry system and then with a temporary extension to Oodnadatta of Woomera’s flight safety system. The paper goes on to describe events following the successful launch, and the celebration of the 50th anniversary in 2017. Finally, there is a discussion of the politics and technologies behind WRESAT.